2022
DOI: 10.1186/s13244-021-01138-8
|View full text |Cite
|
Sign up to set email alerts
|

Active pulmonary tuberculosis: something old, something new, something borrowed, something blue

Abstract: Tuberculosis remains a major global health issue affecting all countries and age groups. Radiology plays a crucial role in the diagnosis and management of pulmonary tuberculosis (PTB). This review aims to improve understanding and diagnostic value of imaging in PTB. We present the old, well-established findings ranging from primary TB to the common appearances of post-primary TB, including dissemination with tree-in-bud nodularity, haematogenous dissemination with miliary nodules and lymphatic dissemination. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
1
15
0
5
Order By: Relevance
“…CS and GS are not necessarily specific to sarcoidosis, and they can also be found in pulmonary tuberculosis, although less frequently than in sarcoidosis 5 6. However, CS and GS in pulmonary tuberculosis correlate with lower isolation of M. tuberculosis 6 7. It has also been reported that smaller CSs are often non-caseous granulomas 3.…”
Section: Discussionmentioning
confidence: 99%
“…CS and GS are not necessarily specific to sarcoidosis, and they can also be found in pulmonary tuberculosis, although less frequently than in sarcoidosis 5 6. However, CS and GS in pulmonary tuberculosis correlate with lower isolation of M. tuberculosis 6 7. It has also been reported that smaller CSs are often non-caseous granulomas 3.…”
Section: Discussionmentioning
confidence: 99%
“…The general good health status of the migrant workforce population may influence this outcome. Moreover, the classic radiographic signs of active TB, such as consolidations, cavitations, and pleural effusions, are often distinctly visible on chest X-rays [ 14 , 15 ], facilitating diagnosis despite technical limitations. In our study, incidental findings unrelated to active TB have been only noted in 4% of the cases, with only 1% being clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The disease spread in PTB can occur endobronchially, through the lymphatics or through the blood vessels [7]. Therefore, we predict that pathophysiology of the occurrence is due to the asymmetry of any of them, either alone or in combination.…”
mentioning
confidence: 98%